Membrane voltage initiates Ca(2+ )waves and potentiates Ca(2+) increases with abscisic acid in stomatal guard cells - Grabov, Alexander (The National Academy of Sciences, 1998)
In higher plants changes and oscillations in cytosolic free Ca(2+) concentration ([Ca(2+)](i)) are central to hormonal physiology, including that of abscisic acid (ABA), which signals conditions of water stress and alters ion channel activities in guard cells of higher-plant leaves. Such changes in [Ca(2+)](i) are thought to encode for cellular responses to different stimuli, but their origins and functions are poorly understood. Because transients and oscillations in membrane voltage also occur in guard cells and are elicited by hormones, including ABA, we suspected a coupling of [Ca(2+)](i) to voltage and its interaction with ABA. We recorded [Ca(2+)](i) by Fura2 fluorescence ratio imaging and photometry while bringing membrane voltage under experimental control with a two-electrode voltage clamp in intact Vicia guard cells. Free-running oscillations between voltages near −50 mV and −200 mV were associated with oscillations in [Ca(2+)](i), and, under voltage clamp, equivalent membrane hyperpolarizations caused [Ca(2+)](i) to increase, often in excess of 1 μM, from resting values near 100 nM. Image analysis showed that the voltage stimulus evoked a wave of high [Ca(2+)](i) that spread centripetally from the peripheral cytoplasm within 5–10 s and relaxed over 40–60 s thereafter. The [Ca(2+)](i) increases showed a voltage threshold near −120 mV and were sensitive to external Ca(2+) concentration. Substituting Mn(2+) for Ca(2+) to quench Fura2 fluorescence showed that membrane hyperpolarization triggered a divalent influx. ABA affected the voltage threshold for the [Ca(2+)](i) rise, its amplitude, and its duration. In turn, membrane voltage determined the ability of ABA to raise [Ca(2+)](i). These results demonstrate a capacity for voltage to evoke [Ca(2+)](i) increases, they point to a dual interaction with ABA in triggering and propagating [Ca(2+)](i) increases, and they implicate a role for voltage in “conditioning” [Ca(2+)](i) signals that regulate ion channels for stomatal function.